Time alignment in speech and speaker recognition - Antanas Lipeika; Joana Lipeikienė (Lietuvos Matematikos Rinkinys)
Time scale alignment problems in speech and speaker recognition by voice are investigated. Dynamic programming approach to solution of this problem is discussed.